The economic impacts of direct payments on agricultural income – A Literature Review - Szerletics, Ákos; Jámbor, Attila (Competitio, 2020)
The economic impacts of direct payments is a widely studied field in the literature related to the Common Agricultural Policy. This article aims to provide a systematic review of the income-related impacts of direct payments. In doing so, the article screened the academic literature on the impacts of direct payments and identified 150 relevant ones, out of which 41 were written directly on income-related effects. Relevant articles can be classified into four groups: general, distributional, stabilisation and other impacts. Most of the literature criticised the ongoing system of direct payments and their effectiveness in producing income-related policy goals. We believe that our results can be useful for researchers and policymakers in better understanding the income-related impacts of direct payments. Journal of Economic Literature (JEL) classification: Q18